1991
DOI: 10.1111/j.0022-3646.1991.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

A NEW PHYLOGENY FOR CHROMOPHYTE ALGAE USING 16S‐LIKE RRNA SEQUENCES FROMMALLOMONAS PAPILLOSA(SYNUROPHYCEAE) ANDTRIBONEMA AEQUALE(XANTHOPHYCEAE)1

Abstract: The 16S‐like ribosomal RNA genes from Mallomonas papillosa Harris et Bradley (Synurophyceae) and Tribonema aequale Pascher (Xanthophyceae) were sequenced and compared to those of other eukaryotes. Mallomonas is closely related to Ochromonas (Chrysophyceae) and supports the general hypothesis of a close phylogenetic relationship between the Synurophyceae and Chrysophyceae. Tribonema is specifically related to Costaria costata (C. A. Agardh) Saunders (Phaeophyceae) demonstrating an unexpected phylogenetic relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 36 publications
5
31
1
Order By: Relevance
“…In this study, the Pelagophyceae are clearly related to the Dictyochophyceae, Pedinellophyceae and Bacillariophyta. Second, previous studies suggested an isolated phylogenetic position for the diatoms (15), whereas our study suggests that they are related to the other reduced-flagellar-apparatus algae. Third, although a relationship between the Dictyochophyceae and Pedinellophyceae was suggested on the basis of ultrastructural features (29), our molecular data and combined data-set analyses provide strong support (bootstrap value = 100) for this relationship.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In this study, the Pelagophyceae are clearly related to the Dictyochophyceae, Pedinellophyceae and Bacillariophyta. Second, previous studies suggested an isolated phylogenetic position for the diatoms (15), whereas our study suggests that they are related to the other reduced-flagellar-apparatus algae. Third, although a relationship between the Dictyochophyceae and Pedinellophyceae was suggested on the basis of ultrastructural features (29), our molecular data and combined data-set analyses provide strong support (bootstrap value = 100) for this relationship.…”
Section: Discussioncontrasting
confidence: 69%
“…Yet, despite the size and significance of the group, evolutionary relationships within the chromophytes went unstudied for decades. During the past 8 years this topic has received attention, based either upon traditional data (i.e., morphology, ultrastructure, and photosynthetic pigments) (3, 4, 10-13) or upon gene sequence data (2,(14)(15)(16). Traditional data sets emphasize…”
mentioning
confidence: 99%
“…1), is confirmed : both groups share a common ancestry highly supported by bootstrap analysis (BP 99 %). The close relationship between xanthophytes and phaeophytes, as previously suggested on the basis of rRNA data (Ariztia et al, 1991 ;Bhattacharya et al, 1992 ;Leipe et al, 1994 ;Saunders et al, 1995 ;Van de Peer & De Wachter, 1997a ;Van der Auwera et al, 1997) is also confirmed (BP 96 %). On the basis of the concatenated sequence alignment, also the chysophytes (represented here solely by Ochromonas danica) and the eustigmatophytes (here represented by Nannochloropsis salina) seem to be sister taxa, highly supported by bootstrap analysis.…”
supporting
confidence: 79%
“…On the basis of the SSU rRNA, the phylogenetic relationships between the different taxa that belong to the so-called heterokont algae cannot be deduced unequivocally (Ariztia et al, 1991 ;Andersen et al, 1993Andersen et al, , 1998Andersen et al, , 1999Potter et al, 1997 ;Lavau et 1997 ; Saunders et al, 1995Saunders et al, , 1997Bailey et al, 1998 ;Van de Peer & De Wachter, 1997a ;Van de Peer et al, 2000a). Therefore, we determined the complete or nearly complete LSU rRNA sequences of several species for which the SSU rRNA sequence was already known.…”
Section: Phylogenetic Relationships Within the Heterokont Algaementioning
confidence: 99%
See 1 more Smart Citation